Functional Profile of Patients with Knee Osteoarthritis at the Physical Medicine and Rehabilitation Clinic of Sanjiwani General Hospital Gianyar - Putu Yogi Astika, Dewa Ngakan; Damayanti, Cendy; Bagus Surianta, I Nengah (Rifa'Institute, 2025)
Introduction: Osteoarthritis (OA) is the most common form of arthritis worldwide, affecting millions and representing a leading cause of disability, particularly among the elderly. In Indonesia, the number of OA cases has more than doubled from 1990 to 2019. However, data on osteoarthritis cases in Bali remain limited. OA is a major cause of joint pain, swelling, and stiffness, leading to decreased quality of life. Objective: This study aims to explore the clinical profile and functional status of patients with knee osteoarthritis to provide a foundational database for future management. Methods: This was a descriptive observational study using a cross-sectional design. Data were collected during a single visit of patients diagnosed with knee OA to the Physical Medicine and Rehabilitation Outpatient Clinic at Sanjiwani General Hospital, Gianyar. Functional status was assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire. Results and Discussion: Most of subjects were aged ≥61 years and predominantly female. Body Mass Index (BMI) ranged from normal to overweight. Most patients worked in the private sector. The WOMAC scores mostly fell within the mild category. Conclusion: The study found that patients with knee OA generally exhibited mild functional impairment, with minimal disruption to daily activities.